From Additive Manufacturing to 3D/4D Printing 3 : Breakthrough Innovations: Programmable Material, 4D printing and Bio-printing - Andre, Jean-Claude, author (Hoboken, NJ : ISTE Ltd/John Wiley and Sons Inc, 2018)
Includes bibliographies and index